International law and the protection of human rights in wartime - Korol’ov, S. S.; Ignatieva, A. I.; Garaz, A. I. (Аналітично-порівняльне правознавство, 2025)
The article is devoted to the pressing issue of ensuring the protection of human rights during armed conflict, particularly in the context of the armed aggression of the Russian Federation against Ukraine. The authors substantiates the need to improve legal mechanisms for the protection of human rights during war, especially under martial law, occupation, and forced displacement of the population. It is noted that violations of human rights and freedoms under such conditions are systemic and large-scale, indicating the insufficient effectiveness of existing international legal instruments. The study covers a broad range of international legal acts governing the protection of human rights during armed conflict. In particular, the importance of international humanitarian law (IHL) and international human rights law (IHRL), their functional correlation, and interaction in times of armed conflict are analyzed. It is emphasized that both branches share a common goal – to ensure the protection of human dignity – but differ in scope and conditions of application. Special attention is given to the right to life as a fundamental and absolute right, which has the status of jus cogens and must be protected even during martial law. The article gives particular focus to the legal regulation of the status of participants in armed conflict (combatants, hors de combat, prisoners of war), as well as the civilian population, which requires special protection. The content of the 1949 Geneva Conventions and their Additional Protocols is revealed, as well as their role in the system of international humanitarian law. It is noted that Ukraine is a party to these international treaties, which entails the obligation to apply them within its domestic legal system, in particular through direct-acting norms and the provisions of the Criminal Code of Ukraine (Article 438 of the Criminal Code of Ukraine). The article also examines practical issues of law enforcement during armed conflict, particularly by the aggressor state. Emphasis is placed on the need for criminal prosecution for violations of IHL norms and the obligation of states to ensure compliance with international standards in the field of human rights protection. The importance of international monitoring mechanisms is underscored, while also pointing out their limited effectiveness, especially in conditions of hybrid warfare and legal uncertainty. The jurisdiction of the European Court of Human Rights (ECtHR) is analyzed separately, along with its approaches to assessing human rights violations during armed conflict. The authors notes that although the ECtHR does not directly apply IHL norms, it evaluates situations in accordance with the provisions of the Convention for the Protection of Human Rights and Fundamental Freedoms, without giving a legal qualification to the actions of the parties to the conflict as war crimes. This indicates a certain divergence in approaches to the qualification of violations. In conclusion, the authors emphasizes the need for harmonization of IHL and IHRL in legal practice, the improvement of protection mechanisms for victims of war, and the strengthening of accountability for violations of legal norms during armed conflicts. It is emphasized that only through the consolidation of efforts by states, international organizations, and civil society can proper protection of human rights during wartime be ensured.